Design Flow Instantiation for Run-Time Reconfigurable Systems: A Case Study. (20th November 2007) - Qu, Yang; Tiensyrjä, Kari; Soininen, Juha-Pekka; Nurmi, Jari
Abstract : Reconfigurable system is a promising alternative to deliver both flexibility and performance at the same time. New reconfigurable technologies and technology-dependent tools have been developed, but a complete overview of the whole design flow for run-time reconfigurable systems is missing. In this work, we present a design flow instantiation for such systems using a real-life application. The design flow is roughly divided into two parts: system level and implementation. At system level, our supports for hardware resource estimation and performance evaluation are applied. At implementation level, technology-dependent tools are used to realize the run-time reconfiguration. The design case is part of a WCDMA decoder on a commercially available reconfigurable platform. The results show that using run-time reconfiguration can save over 40% area when compared to a functionally equivalent fixed system and achieve 30 times speedup in processing time when compared to a functionally equivalent pure software design.